Testing Agronomic Treatments to Improve the Establishment of Novel Miscanthus Hybrids on Marginal Land - Eva Lewin; John Clifton-Brown; Elaine Jensen; Iris Lewandowski; Jacek Krzyżak; Marta Pogrzeba; Jens Hartung; Cedric Wolfmüller; Andreas Kiesel (Agronomy, 2025)
Miscanthus is considered a promising candidate for the cultivation of marginal land. This land poses unique challenges, and experiments have shown that the “establishment phase” is of paramount importance to the long-term yield performance of miscanthus. This experiment analyzes novel miscanthus hybrids and how their establishment on marginal land can be improved through agronomic interventions. Experiments took place at two sites in Germany: at Ihinger Hof, with a very shallow soil profile and high stone content, and at Reichwalde, where the soil was repurposed river sediment with low organic matter, high stone content, and a compacted lower horizon. These marginal conditions functioned as test cases for the improvement of miscanthus establishment agronomy. Four hybrids (Miscanthus x giganteus, Gnt10, Gnt43, and Syn55) and agronomic treatments such as plastic mulch film, miscanthus mulch, inoculation with mycorrhizal fungi, and fertilization were tested in two years at both sites in 2021 and 2022. Specific weather conditions and the timing of planting were strong determinants of establishment success and no single treatment combination was found that consistently increased the establishment success. Plastic mulch films were found to hinder rather than help establishment in both these locations. Chipped miscanthus mulch caused nitrogen immobilization and stunted plant growth. At Ihinger Hof the novel seed-based miscanthus hybrid Gnt43 produced twice the biomass of other hybrids (7 t ha−1) in the first growing season. Gnt10 yielded well in 2021 and showed impressive tolerance to water stress in the summer of 2022. No treatment combination was found that consistently increased the establishment success of miscanthus hybrids across sites and years. Novel genotypes consistently outperformed the standard commercial miscanthus hybrid Miscanthus x giganteus. Gnt10 may be a promising candidate for the cultivation of water-stress-prone marginal lands, due to its isohydric behavior and high yield potential.